HISTOMORPHOLOGICAL STATUS OF THE PLACENTA AND FEATURES OF PLACENTAL DEVELOPMENT UNDER THE INFLUENCE OF ZINC CHLORIDE IN EXPERIMENTAL ANIMALS - Beletskaya, E.N.; Onul, N.M.; Shatornaya, V.F.; Kononova, I.I.; Demura, E.V. (World of Medicine and Biology, 2014)
The article contains the results of study of the morphofunctional state of placenta and features of placental development under the influence of zinc chloride in a dose 1,5 mgs/of kg by means of daily intragastric tube from 1 to 19th day of pregnancy. It is revealed, that additional introduction of these doses of zinc not only does not violate the processes of fetoplacental complex forming and histostructure of placenta, but even possesses some stimulant action, that provides development of placenta within the limits of high bounds of control values.